(untitled) (Research, Society and Development, 2020)
The present work is a clinical case report of a patient who presented tooth 16 with a high degree of damage and distal wall at the subgingival level. Therefore the research aims to facilitate the understanding of the Deep Margin Elevation (DME) technique and spread it to undergraduates and professionals dental area. The elevation of the gingival margin consists of a simple and effective technique, where surgical steps are not necessary to establish the maintenance and preservation of the periodontium. The technique allows the elevation of the subgingival margin, there must be 3 mm of integrated dental structure above the alveolar crest, respecting the junctional epithelium dimension and conjunctive insertion. The DME must follow a correct protocol, taking into account the correct selection of materials in order to maintain homeostasis in the region as well as making a well-adapted and polished restoration. It is concluded that DME is a very useful technique in the treatment of damaged struction at the subgingival level, avoiding in certain cases invasive procedures aiming at the preservation of the dental structure. With this, the objective of the present work is to demonstrate through a clinical case the DME technique so that it facilitates the understanding on the subject and that it contributes for students and dental professionals to be able to reproduce the technique in their daily routine.